2016
DOI: 10.15184/aqy.2015.191
|View full text |Cite
|
Sign up to set email alerts
|

Trade me an axe? Interpretive challenges of the distribution and provenance of Neolithic basaltic bifacial tools in Israel

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 33 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Previous geochemical-mineralogical studies of basalt artefacts in the southern Levant concentrated mainly on the determination of the provenance of the artefacts, but these studies always had rather limited results due to the fact that basaltic rock extraction sites had not been identified (apart from the Late Neolithic-Early Chalcolithic extraction site at Giv'at Kipod, see Rosenberg et al 2008;Gluhak & Rosenberg 2013;Rosenberg & Gluhak 2016;Shimelmitz & Rosenberg 2016) and that geochemical data from geological samples for comparison were, if available at all, only superficially included (e.g., Amiran & Porat 1984;Philip & Williams-Thorpe 1993;2000;2001;Rowan 1998;Rutter 2003;Rutter et al 2003;Watts et al 2004;Rutter & Philip 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous geochemical-mineralogical studies of basalt artefacts in the southern Levant concentrated mainly on the determination of the provenance of the artefacts, but these studies always had rather limited results due to the fact that basaltic rock extraction sites had not been identified (apart from the Late Neolithic-Early Chalcolithic extraction site at Giv'at Kipod, see Rosenberg et al 2008;Gluhak & Rosenberg 2013;Rosenberg & Gluhak 2016;Shimelmitz & Rosenberg 2016) and that geochemical data from geological samples for comparison were, if available at all, only superficially included (e.g., Amiran & Porat 1984;Philip & Williams-Thorpe 1993;2000;2001;Rowan 1998;Rutter 2003;Rutter et al 2003;Watts et al 2004;Rutter & Philip 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, as stated above, these studies reflect the potential of provenance studies while also demonstrating the problems inherent in these studies, in particular the need for a reliable geochemical database of basalt sources. A large-scale project was recently initiated that focuses on establishing the geochemical signature of basalt sources in Israel using a basanite bifacial tool quarry and production site in the Manasseh Hills at the western fringes of the Jezreel Valley as a test case for the chosen methodology (Gluhak & Rosenberg 2013;Rosenberg & Gluhak 2016). The results of the study proved that a highresolution sampling strategy, the geochemical analyses chosen, and statistical, multivariate analyses (see methodology section, below), provide a good combination for studying the provenance of basaltic tools.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a variety of raw materials to manufacture a specific tool type characterized the production of bifacial tools in the southern Levant. Although primarily made of flint (e.g., Barkai 2005), some were produced on basaltic rocks, limestone, and other more 'exotic' raw materials (e.g., Garfinkel & Dag 2006;Rosenberg et al 2008;Rosenberg & Gopher 2010;Gluhak & Rosenberg 2013;Rosenberg and Gluhak 2015;Vardi 2015).…”
Section: Raw Materials and Bifacial Tools In The Southern Levantmentioning
confidence: 99%
“…Currently, Giv'at Kipod is the only known quarry and production site for basaltic bifacial tools in the southern Levant, although a recent geochemical study showed that other locals also served this purpose (Gluhak & Rosenberg 2013;Rosenberg and Gluhak 2015). Similar sites, exploiting non-flint resources, are also rare and include three larnite quarry and bifacial production sites in the Negev of Israel (Vardi 2015), and others, much northern sites in Turkey, Thrace (e.g., Özbek 2000Özbek , Özbek & Erol 2001.…”
Section: The Uniqueness Of Giv'at Kipod In Terms Of the Extraction Ofmentioning
confidence: 99%
See 1 more Smart Citation